Photoactivatable Nanobody Conjugate Dimerizer Temporally Resolves Tiam1‐Rac1 Signaling Axis - Chengjian Zhou; Huiping He; Xi Chen (Advanced Science, 2024)
Abstract The precise spatiotemporal dynamics of protein activities play a crucial role in cell signaling pathways. To control cellular functions in a spatiotemporal manner, a powerful method called photoactivatable chemically induced dimerization (pCID) is used. In this study, photoactivatable nanobody conjugate inducers of dimerization (PANCIDs) is introduced, which combine pCID with nanobody technology. A PANCID consists of a nanobody module that directly binds to an antigenic target, a photocaged small molecule ligand, and a cyclic decaarginine (cR10*) cell‐penetrating peptide (CPP) for efficient nonendocytic intracellular delivery. Therefore, PANCID photodimerizers also benefit from nanobodies, such as their high affinities (in the nm or pm range), specificities, and ability to modulate endogenous proteins. Additionally it is demonstrated that the nanobody moiety can be easily replaced with alternative ones, expanding the potential applications. By using PANCIDs, the dynamics of the Tiam1‐Rac1 signaling cascade is investigated and made an interesting finding. It is found that Rac1 and Tiam1 exhibit distinct behaviors in this axis, acting as time‐resolved “molecular oscillators” that transit between different functions in the signaling cascade when activated either slowly or rapidly.